2011
DOI: 10.4103/0019-5545.82538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics of migraine and tension type headache

Abstract: Context:Migraine and tension type headache (TTH) are two most common types of primary headaches. Though the International Classification of Headache Disorders-2 (ICHD-2) describes the diagnostic criteria, even then in clinical practice, patients may not respect these boundaries resulting in the difficulty in diagnosis of these pains.Materials and Methods:This cross-sectional study involved 50 subjects in each of the two groups – migraine and TTH – after screening for the inclusion and exclusion criteria. Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…In line with some previous studies, the present study revealed the highest frequency of pain among migraine patients compared to the patients suffering from other types of headache (25,26). The percentage of pain chronicity in migraine was also higher than cluster and tension type headache.…”
Section: Discussionsupporting
confidence: 93%
“…In line with some previous studies, the present study revealed the highest frequency of pain among migraine patients compared to the patients suffering from other types of headache (25,26). The percentage of pain chronicity in migraine was also higher than cluster and tension type headache.…”
Section: Discussionsupporting
confidence: 93%
“…[2] Migraine is a common disorder which has psychiatric sequelae. [36] The psychic manifestations of migraine, including confusion, depression, memory impairment, drowsiness, fearfulness and ill humour were described more than a century ago. [7] In further studies,[813] general distress, anxiety, fear of impending doom, depression, irritability, fatigue, lethargy, apathy, dullness, changes in motor activity, appetite and sleep have been reported.…”
mentioning
confidence: 99%
“…Since, findings from clinical investigation of an episode were unspecified disease with psychiatric disorder, migraine head ache, and syncope. An important feature of migraine and syncope was their co-morbidity with mass psychogenic illness and other neurological diseases [23][24][25][26].Similar incident was reported from South Africa, Malawi [27,28] but unlike the current incident due to infectious disease was reported from the village of India, West…”
Section: Discussionmentioning
confidence: 75%